Multipoint MMS observations of fine‐scale SAPS structure in the inner magnetosphere. Issue 14 (18th July 2016) - Erickson, P. J.; Matsui, H.; Foster, J. C.; Torbert, R. B.; Ergun, R. E.; Khotyaintsev, Yu. V.; Lindqvist, P.‐A.; Argall, M. R.; Farrugia, C. J.; Paulson, K. W.; Strangeway, R. J.; Magnes, W.
Abstract: We present detailed observations of dynamic, fine‐scale inner magnetosphere‐ionosphere coupling at ∼3.9  R E in the Region 2 Birkeland field‐aligned current (FAC). We find that observed electrodynamic spatial/temporal scales are primarily characteristic of magnetically mapped ionospheric structure. On 15 September 2015, conjugate Magnetospheric Multiscale (MMS) spacecraft and Millstone Hill radar observations show plasmasphere boundary region subauroral polarization stream (SAPS) electric fields at L = 4.0–4.2 near 21 MLT. MMS observations reveal high‐altitude ∼1 mV/m fine‐scale radial and azimuthal electric field perturbations over ≤0.15 L with high spatial coherence over ≥2–3 min and show outward motion within a broader FAC of ∼0.12 μA/m 2 . Our analysis shows that MMS electric field fluctuations are most likely reflective of SAPS ionospheric structure at scales of ∼22 km and with ionospheric closure of small‐scale filamentary FAC perturbations. The results highlight the ionosphere's importance in regulating fine‐scale magnetosphere‐ionosphere structure. Key Points: SAPS electric fields have small‐scale structure in the plasmasphere boundary region SAPS perturbations can have spatiotemporal structure governed by the ionosphere SAPS Region 2 filamentary current closure may occur on ∼22 km ionospheric spatial scales